Water Quality Assessment of the Semenyih River, Selangor, Malaysia. (24th August 2013) - Al-Badaii, Fawaz; Shuhaimi-Othman, Mohammad; Gasim, Muhd Barzani
Abstract : This study was carried out to determine the Semenyih River water quality based on the physicochemical and biological parameters. The sampling was conducted in dry and rainy seasons during 2012. Water samples were collected from 8 stations along the river and analyzed using standard methods. The results showed that temperature, pH, conductivity, TDS, SO4, and TH were classified as class I, while DO, turbidity, and BOD were categorized under class II, and NH3 -N, TSS, COD, and OG were categorized as class III based on NWQS, Malaysia. Moreover, NO3 was classified under class IV, while PO4 and FC were categorized as class V and exceeded the allowable threshold levels. Therefore, the river was slightly polluted with NH3 -N, TSS, COD, and NO3, whereas it is extremely contaminated with PO4 and FC. Furthermore, cluster analysis classified 8 sampling stations into three clusters based on similarities of water quality features. Furthermore, factor analysis of the water quality datasets generated three factors with total variance of 94.05% and pointed out that water quality deterioration in the river was associated with industrial and agricultural activities, livestock farming, and erosion. Therefore, the river water can be used for irrigation with precaution but extensive treatment needed before using for domestic purposes.